Seeing the image of one’s culture through the image of another: translating images of national identity - Giugliano, Marcello; Alsina Keith, Victòria (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
In this article we combine the frameworks provided by Imagology and Translation Studies in order to analyze how translation can work as a tool of image formation and manipulation. Our paper focuses on the main features of the image of Irish national identity as it is represented in Brian Friel’s play Translations and on the way these features have been translated into Catalan. Through a contrastive analysis of the source text and the target text, we examine the changes to these features that occurred during the translation process and the impact they have had on the constitution of the image of Irishness in the Catalan culture. We then consider the relationship established in the target culture between the self-image of Catalan national identity and the hetero-image of the Irish one. Finally, we propose a refinement of the taxonomy commonly used to describe images of national identities and their relationship of reciprocity or opposition.